2012
DOI: 10.1021/bm300912y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Solvent Parameters in the Regeneration of Cellulose from Ionic Liquid Solutions

Abstract: The ionic liquids 1-ethyl-3-methylimidazolium acetate [emim]OAc, N,N,N,N-tetramethylguanidium propionate [TMGH]EtCO(2), and N,N,N,N-tetramethylguanidium acetate [TMGH]OAc, and the traditional cellulose solvent N-methylmorpholine N-oxide NMMO were characterized for their Kamlet-Taft (KT) values at several water contents and temperatures. For the ionic liquids and NMMO, thresholds of regeneration of cellulose solutions by water were determined using nephelometry and rheometry. Regeneration from wet IL was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
230
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(241 citation statements)
references
References 62 publications
9
230
0
2
Order By: Relevance
“…A slight shielding of the methylene carbons in the α position were also observed when converting the amine δ = 45.9 ppm (2C) and δ = 54.8 ppm (1C) to the IL δ = 45.3 ppm (2C) and δ = 54.6 ppm (1C PO 4 ] were also selected based on their subtle differences in polarity and substituent effects. The polarity of an IL has been correlated with its ability to solubilize both lignin (42,43) and cellulose (44)(45)(46) PO 4 ] were used to dissect the role of these substituents on the relative acidity of the cation and relate these effects to biomass pretreatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A slight shielding of the methylene carbons in the α position were also observed when converting the amine δ = 45.9 ppm (2C) and δ = 54.8 ppm (1C) to the IL δ = 45.3 ppm (2C) and δ = 54.6 ppm (1C PO 4 ] were also selected based on their subtle differences in polarity and substituent effects. The polarity of an IL has been correlated with its ability to solubilize both lignin (42,43) and cellulose (44)(45)(46) PO 4 ] were used to dissect the role of these substituents on the relative acidity of the cation and relate these effects to biomass pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…Kamlet-Taft solvent parameters have been used to measure the ability of a solvent to donate a hydrogen bond (α), and accept a hydrogen bond (β) (51). It has been shown that basicity (β) correlates well with an IL's ability to dissolve lignocellulose (52), and that net basicity correlates with an IL's ability to dissolve cellulose (46,53). A recent experimental study on a range of cations in combination with the same anion demonstrated that cation acidity is also important for cellulose dissolution (54) PO 4 ], one would expect the differential substitution of the electron-donating groups to affect the N atom's affinity for the H 3 PO 4 proton.…”
Section: Compositional Analysis Of Untreated and Pretreated Switchgrassmentioning
confidence: 99%
“…The possibility to pair anions with cations yields an almost endless library of ILs, and they are used in numerous fields, such as separation technology, electrochemistry, catalysis, and as solvents [3,4]. In the last decade, ILs as solvents for biomass in general and cellulose in particular have been widely investigated [5][6][7] since 2002 when Swatloski published the pioneering work on dissolution of cellulose in 1-butyl-3-methylimidazolium chloride (BMIMCl) [8]. This relatively new solvent class has shown great versatility in the field of cellulose technology, including dissolution for regeneration purposes [9,10], homogeneous derivatization [11,12], and biomass processing including wood component separation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent molecular dynamics simulations, carried out on cellulose oligomers and 1-ethyl-3-methylimidazolium acetate (C2mimOAc), indeed suggest that the cations are in close contact with the cellulose through hydrophobic interactions (Liu et al 2010). Closely related, Hauru et al found that cellulose regeneration from IL solutions goes via the hydrophobic association of the less polar regions of cellulose (Hauru et al 2012). An interesting work of Mostofian et al suggests a synergistic approach for cellulose dissolution in IL (Mostofian et al 2014).…”
Section: Cellulose Amphiphilicity and Hydrophobic Interactions: A Brimentioning
confidence: 91%